RE-APPRAISING THE ROLE OF PHILOSOPHICAL BASES FOR TEACHING ENGLISH REFLECTED IN THE CURRENT CURRICULUM IN INDONESIA (Language Circle: Journal of Language and Literature, 2011)
This article discusses the philosophical bases of the current curriculum—School-Based Curriculum, which is considered as the simplified version of the previous—Competency Based Curriculum. The aim of this discussion is primary to re-visit the theories that teacher may have overlooked. It also deals with possible application of the theories in the real teaching and learning of English. Hopefully, this may contribute to the understanding of the current curriculum better. Keywords: curriculum, communicative competence, systemic functional linguistics, ZPD, literacy education